2021
DOI: 10.1177/10711007211040820
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Middle Facet Subluxation and Foot and Ankle Offset in Progressive Collapsing Foot Deformity

Abstract: Background: Subtalar middle facet (MF) subluxation was recognized as a reliable marker for progressive collapsing foot deformity (PCFD) diagnosis. Foot and Ankle Offset (FAO) is an established measurement, predictive of malalignment severity. The objective of this study was to assess the potential association between MF subluxation and FAO in PCFD patients. Methods: 56 individuals with flexible PCFD (74 feet) were assessed. Two blinded foot and ankle surgeons calculated MF uncoverage, MF incongruence, and FAO.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The middle facet of the subtalar joint can now be reliably evaluated using weight-bearing CT scans, and de Cesar Netto et al 45 established that the middle facet represents a particularly sensitive location to detect early peritalar subluxation in progressive collapsing flatfoot deformity. Barbachan Mansur et al 46 further showed that middle facet subluxation is correlated with foot and ankle offset, a well-established measure of global hindfoot alignment on weight-bearing CT scans. Middle facet subluxation of 27.5% represented a threshold that correlated with higher foot and ankle offset values, suggesting hindfoot collapse.…”
Section: Progressive Collapsing Flatfoot Deformitymentioning
confidence: 99%
“…The middle facet of the subtalar joint can now be reliably evaluated using weight-bearing CT scans, and de Cesar Netto et al 45 established that the middle facet represents a particularly sensitive location to detect early peritalar subluxation in progressive collapsing flatfoot deformity. Barbachan Mansur et al 46 further showed that middle facet subluxation is correlated with foot and ankle offset, a well-established measure of global hindfoot alignment on weight-bearing CT scans. Middle facet subluxation of 27.5% represented a threshold that correlated with higher foot and ankle offset values, suggesting hindfoot collapse.…”
Section: Progressive Collapsing Flatfoot Deformitymentioning
confidence: 99%
“…The recent use of WBCT to evaluate PTS has produced important data to help understand this pathological functioning 11 , 12 . Using two-dimensional tools in coronal plane imaging, the amount of subluxation at the posterior and middle facets was found to be correlated with PCFD diagnosis and severity 6 , 11 , 13 , 14 . Dibbern et al performed an objective three-dimensional (3D) WBCT analysis of the subtalar joint in PCFD using 3D distance maps (DMs) and introducing the concept of coverage mapping (CM) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Foot and ankle offset (FAO) is a three-dimensional (3D) measurement for overall foot and ankle alignment assessment. It is characterized by the relation between the weight-bearing tripod of the foot and the center of the ankle joint (1)(2)(3) . The most plantar voxel of the heads of the fifth and first meta-tarsal and the calcaneal tuberosity make up the tripod of the foot, while the most proximal and central points of the talus represents the center of the ankle.…”
Section: Introductionmentioning
confidence: 99%
“…The FAO is clinically relevant due to its ability to produce an objective value portraying the foot alignment (3)(4)(5) . In addition, it represents a measurement of the offset between the body weight vector and the ground reaction force vector, thus making it a biomechanically relevant measurement.…”
Section: Introductionmentioning
confidence: 99%